IMPLIKASI PENERAPAN PERATURAN GUBERNUR NOMOR 42 TAHUN 2017 TERHADAP PENINGKATAN PENERIMAAN PAJAK KENDARAAN BERMOTOR DI SAMSAT MANADO - Wondal, Meilani; Lambey, Linda; Wangkar, Anneke (Universitas Sam Ratulangi, 2018)
The motor vehicle tax amnesty is one of the policies which can be issued by local government to improve its motor vehicle tax revenue. In 2017, local government of North Sulawesi, in this case the Governor of North Sulawesi, issued the Governor Regulation Number 42 Year 2017 about motor vehicle tax amnesty and ownership relocation customs. The purpose of this research is to observe the implication process of applying Governor Regulation Number 42 Year 2017 towards the improvement of motor vehicle tax revenue at SAMSAT Manado. Qualitative research method was used with descriptive analysis method to describe the realization of motor vehicle tax revenue using table and diagram before and after tax amnesty which the conclusion was drawn later. The research outcome showed that motor vehicle tax revenue improved due to tax amnesty program even though its implication was not really considerable only 2.028% of the total revenue of motor vehicle tax in 2017. Keywords: Motor Vehicle Tax Amnesty, Implication, Motor Vehicle Tax Revenue.